HAKIKAT ILMU DALAM AL-QUR’AN SERTA IMPLIKASINYA DALAM KEHIDUPAN SEHARI-HARI - Nasywa Dhiya’ ul Aulia; Zulfatur Roja; Usman Abdullah; Ana Rahmawati (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2025)
The Qur’an is the holy book of Muslims which discusses various things, including the nature of science. This study analyses verses from surah Hud verse 14, Al- Baqarah verses 32 and 145, and Al- Qashash verse 78. These verses provide an indept understanding of the concept of knowledge in islam which includes the relationship between in the Creator humans, the universe, and humanity. Knowledge is given as Allah Swt’s greatest gift to humans to distinguish humans from other creatures, and as a means to achive happinesin this world and thehereafter . it is important to practice knowledgein a benefical way in everyday life, because in the Qur’an science is not only knowledge, but also worship, morality and social responsibility. If someone truly understands what knowledge means, the will be more motivated to continue learning and developing, and they will utilize their knowledge for benefit of humanity.